Perceived Benefits, Risks and Acceptability of Online Lending as Financing Source Among Micro, Small, Medium Enterprises (MSME) in General Santos City - Pena, Jayvee G.; Salise, Kerby P. (International Journal of Research in Interdisciplinary Studies, 2025)
This quantitative research investigated the benefits, acceptability and risks of online lending as a financing option among Micro, Small, and Medium Enterprises (MSMEs) in General Santos City. With the rise of FinTech platforms and challenge to traditional financing options, this research sought to explore the perspective of MSMEs towards online lending applications. Data was gathered through validated survey questionnaires from a sample of 272 owners of businesses using correlational design. Despite having high awareness of online lending, actual usage was extremely low which was one of the findings. Both the benefits and risks of online lending were captured by the respondents and viewed as moderate. Key benefit factors like profit and growth, and flexibility and customization were closely associated with acceptability, while security and privacy concerns, collection methods, and transparency were also linked to risk dimensions related to acceptance levels. These findings indicate that online lending still has prospects, but the MSMEs’ lack of experience with the system as well as their more guarded viewpoint toward risk limits its implementation. This study emphasizes the importance of achieving adequate transparency and financial literacy as well as better regulation to improve trust and FinTech adoption by local businesses.